Analisis pengelolaan bantuan langsung tunai di Desa Sendangan dan Desa Talikuran Kecamatan Tompaso - Tujuwale , Samuel Daniel; Warongan , Jessy D.L; Pangerapan, Sonny (Yayasan Widyantara Nawasena Raharja, 2024)
Direct Cash Assistance is a social assistance program provided by the government in the form of cash assistance or other assistance to people in need. The research objective in this study is to analyze the management of Direct Cash Assistance in Sendangan Village and Talikuran Village Based on Minister of Finance Regulation Number 201 of 2022. This research uses qualitative research with a descriptive approach. This research shows that the Government of Sendangan and Talikuran Village can be said to be in accordance with governance regulated in Minister of Finance Regulation Number 201 concerning Direct Cash Assistance, starting from the stages of allocation, distribution, administration, reporting, to accountability, is deemed to have followed the applicable provisions and can do everything well, but can still be improved further for transparency with society by empowering modern technology.